2017
DOI: 10.4103/cytojournal.cytojournal_17_17
|View full text |Cite
|
Sign up to set email alerts
|

A case of large cell neuroendocrine carcinoma of the uterine cervix misdiagnosed as adenocarcinoma in Thinprep cytology test

Abstract: Large cell neuroendocrine carcinoma (LCNEC) of uterine cervix is a rare malignancy with aggressive behavior and poor clinical outcome even in its early stage. Few cytopathologic features of cervical LCNEC have been reported previously. A 57-year-old postmenopausal African American female, presented to the local health department with a chief complaint of heavy vaginal bleeding. A 45-year-old female presented with 20 months of vaginal pruritus and foul odor. Cervical malignancy was suspected by pelvis magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…LCNECs of the uterine cervix are very rare with only 40 cases reported in the literature, although their misdiagnosis, notably as poorly differentiated adenocarcinoma, has also been reported, making the actual prevalence of LCNECs potentially higher. 5,6 Besides, it has been reported that AIS or invasive adenocarcinoma can accompany LCNECs 5 with 8 and 3 cases, respectively, reported in 12 LCNEC patients. 7 Studies reveal that neuroendocrine differentiation in glandular lesions of the cervix is not uncommon.…”
Section: Polypectomy Materials and A Cervicovaginal Smear Was Sent To...mentioning
confidence: 99%
“…LCNECs of the uterine cervix are very rare with only 40 cases reported in the literature, although their misdiagnosis, notably as poorly differentiated adenocarcinoma, has also been reported, making the actual prevalence of LCNECs potentially higher. 5,6 Besides, it has been reported that AIS or invasive adenocarcinoma can accompany LCNECs 5 with 8 and 3 cases, respectively, reported in 12 LCNEC patients. 7 Studies reveal that neuroendocrine differentiation in glandular lesions of the cervix is not uncommon.…”
Section: Polypectomy Materials and A Cervicovaginal Smear Was Sent To...mentioning
confidence: 99%